HIF-1Α IN SALIVA: A PROMISING BIOMARKER FOR EARLY DIAGNOSIS OF ORAL SUBMUCOUS FIBROSIS AND ITS MALIGNANT POTENTIAL - ASKARY, GR; ASKARY , SH; ZAREEF , U; YASMEEN, U; KHAN , S; IMTIAZ , SA (Biological and Clinical Sciences Research Journal, 2024)
Oral submucous fibrosis (OSF) is a chronic condition with a high risk of transforming into oral squamous cell carcinoma (OSCC). Identifying reliable biomarkers for early diagnosis and monitoring of OSF is crucial for malignancy prevention. Objective: This study evaluates the expression of Hypoxia Inducible Factor-1α (HIF-1α) in saliva as a potential biomarker for OSF. Methods: Study was a cross-sectional study conducted in Karachi. The study was completed in 6 months from July 2023 to December 2023 and Sixty-five OSF patients participated in the study, providing saliva samples analyzed for HIF-1α expression using immunohistochemically (IHC). Clinic pathological features, including age, gender, body mass index (BMI), and etiological factors (tobacco, smoking, areca nut), were documented. Relationships between clinical symptoms (burning sensation, pain, ulceration, and dry mouth), fibrosis severity, and HIF-1α staining intensity in blood vessels and fibroblasts were assessed. Results: The study population included 68.3% males and 31.7% females, with a mean age of 32.56±4.12 years. Tobacco use (47.7%) was the most common etiology. HIF-1α expression was significantly elevated in fibroblasts compared to blood vessels, with mild staining in 54.2% of blood vessels and 49.8% of fibroblasts. Increased HIF-1α expression correlated with more severe OSF symptoms, indicating a higher risk of malignant transformation. Conclusion: HIF-1α is a promising biomarker for early diagnosis and assessment of malignant potential in OSF. Early detection and monitoring could improve clinical management and reduce OSCC risk, warranting further research for validation and therapeutic targeting.